Micro- and macroclimatic temperature with species data of saproxylic beetles in Swedish forests ... : Temperaturmätningar av mikro- och makroklimat samt artdata för vedlevande skalbaggar från svenska skogar ... - Gossmann, Anika; Ranius, Thomas; Schroeder, Martin; Öckinger, Erik; Lindman, Ly (Swedish University of Agricultural Sciences, 2025)
From May until September 2020, micro- and macroclimatic temperature were measured along a 1200 km latitudinal gradient in Sweden. Microclimatic temperature was measured hourly under the bark of spruce logs, while macroclimatic temperature refers to measured air temperature 1.3 m above the ground at the same study sites. From April until September 2021, saproxylic beetles were collected at these study sites. The data set "boreal_forest_climate_data" contains 12 columns and 88 rows. Block: six different study sites are distributed from southern (1) to northern Sweden (6). Plot: five study plots that contains one study site. Block 1: Plot 11-15 Block 2: Plot 6-10 Block 3: 16-20 Block 4: 21-25 Block 5: 1-5 Block 6: 26-30 Shade: three different shade level at one plot. 1: sun-exposed, 2: intermediately shaded and 3: fully-shaded. Mikro- and makrotemp: mean temperatures per Block, plot and shade. CTI: community temperature index per Block, plot, and shade. Bark: Remaining bark at every spruce log. Diameter: ... : Temperaturmätningar av mikro- och makroklimat har gjorts på sex skogslokaler i Sverige längs en 1200 km lång latitudinell gradient från maj till september 2020. Mikroklimatets temperatur mättes varje timme under barken på granstockar, och makroklimatets temperatur mättes som lufttemperaturen 1,3 m ovanför marknivå på samma platser. Från april till september 2021 samlades vedlevande skalbaggar in från granstockar på skogslokalerna. boreal_forest_climate_data.csv innehåller temperaturdata från mätningar av mikro- och makroklimat, och specieslist_xylo.csv innehåller artdata. Filerna använder sig av semikolon som separatortecken. Se den engelska versionen av databeskrivningen samt dokumentationsfilen readme.txt för detaljerade kolumnbeskrivningar. ...